Analytical study on the marketing strategies of mobile phone service providers in Singapore. - Ng, Yean Hoon. (2008)
The aim of our research is to examine the marketing strategies of mobile phone service providers (MPSPs)--SingTel Mobile (STM) and M1, analyze their strengths and weaknesses, and discuss the future strategic direction of MPSPs in Singapore (currently, they are STM, M1 and StarHub).